Caracteristicas basicas do material cartografico empregado em atividades agronomicas nas bacias hidrograficas - Politano, W.; Demetrio, V. A.; Lopes, L. R. (My University, 1989)
Covers cartographic aspects related to characterization and map-making of watersheds, in surveys relating to agronomic activities. The recommendations, about scales and others specifications of thematic maps, were established in conformity with the dimension and complexity of watershed. -English summary
The basic characteristics of cartographic material employed in agronomic activities in the watersheds
Keywords: agronomic study; map scale; thematic map; watershed characterisation